The society of information and communication in education: Speeches configuring the teacher for virtual education: Subjective and subjectivity - Benitez-Saza, Claudia Rocio; Bustos-Velazco, Edier; Arevalo-Gomez, Edgar (Revista Científica, 2018)
This article is part of the results of the research on the Educator in Colombia for Virtual Education from the analysis of the Information Society and Knowledge; the following study and structure on three moments of analysis on the breakthrough of Technology in the field of education; the first, investigates and traces the discursive practices that shape the Virtual Educator and how the virtual emerges in the history of Colombian education; in the second, we chose the archeological-genealogical method, methodological arsenal that distances itself from the transcendental conception of history, to make an analysis of the regimes that establish, normalize, naturalize and legitimize the permanent presence of Technology in Education in the discursive field of Virtuality. In the third moment, the results are presented and it is concluded from the discourses that show the power strategy of the Society of Information and Communication in education.